IMPLEMENTASI KEBIJAKAN PROGRAM KELUARGA HARAPAN DALAM PENGENTASAN KEMISKINAN DI KECAMATAN ENOK KABUPATEN INDRAGIRI HILIR PROVINSI RIAU - jurnalmap map; Wage Taurusandika; Hadi Susanto; Sri Mulyani (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2021)
This research is to find out how the Policy Implementation of the Family Hope Program as well as the supporting and inhibiting factors in the Implementation of the Policy on the Family Hope Program in Enok District, Indragiri Hilir Regency, Riau Province. This type of research is a qualitative approach and focuses on whether or not the problem is easy to work on in the implementation of PKH, the ability of PKH policies to structure the implementation process properly, factors outside the policy that affect the PKH process. Informants in this study were PKH Implementers and PKH Beneficiary Families. Data was collected by using observation, interview and documentation methods. The results showed that the condition of PKH participants in Enok Subdistrict since the implementation of PKH in Enok Subdistrict, Indragiri Hilir Regency, Riau Province experienced ease in accessing health and education facilities, another perceived benefit was as additional capital for their socio-economic life.